Stress and guarantee of the right to health of military police: a systematic review (Research, Society and Development, 2021)
Understanding stress raises the conditions for improving the quality of life of military police officers. Thus, this work aims to identify how stress is presented in military police, described in scientific productions. This is a systematic literature review, where the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria were adopted. The search strategy adopted was an investigation of articles in electronic databases: Lilacs, Scielo and Medline/PubMed. The terms used in the research were based on Health Sciences descriptors (DECs), considering the following words: “military police” OR “policía militar” OR “polícia militar” AND “psychological stress” OR “Estrés Psicológico” OR “Estresse Psicológico". The inclusion criteria adopted in this research were: the article should be indexed in the selected databases and available in full English, Spanish or Portuguese; with survey participants of any gender and age; quantitative and/or qualitative research. It was observed that interpersonal interaction based on hostility characteristics, problems with the hierarchy, high work demand and gender bias were identified stress generators. Studies show that the police presented stress with psychological symptoms and physical symptoms. In this context, it is suggested that the elaboration of actions to promote health and prevent mental disorders in military police officers are necessary in order to improve the working conditions that generate stress.